Gold nanoparticles loaded on TiO2 nanoparticles doped with N2 as an efficient electrocatalyst for glucose oxidation: preparation, characterization, and electrocatalytic properties - Yasmin M. S. Jamil; Mohammed Ahmed Hussein Awad; Hussein M. A. Al-Maydama; Ahmed N. Alhakimi; Mohamad M. E. Shakdofa; Samir Osman Mohammed (Journal of Analytical Science and Technology, 2022)
Abstract A powder of titanium oxide nanoparticles (TiO2 NPs) was synthesized in this study by anodizing in 0.7 M HClO4 and then annealing in N2 at 450 °C for 3 h to produce TiO2 NPs-N2 powder as a catalyst. These TiO2 NPs-N2 nanoparticles were then encrusted with Au nanoparticles utilizing the photodeposition procedure with tetrachloroauric acid (HAuCl4) and isopropanol as sacrificial donors. With a surface area of 121 m2g−1, the Au NPs/TiO2 NPs-N2 powder catalyst has a high surface area, according to the Barrett–Joyner–Halenda technique. According to X-ray diffraction (XRD) analysis, TiO2 NPs-N2 contained uniformly integrated Au nanoparticles with an average crystallite size of about 26.8 nm. The XRD patterns showed that the prepared Au NPs/TiO2 NPs-N2 were crystallites and nano-sized. The transmission electron microscopy image revealed the spherical shape of the nanoparticles and their tendency for agglomeration. Utilizing the cyclic voltammetry, the electrochemical properties of the catalyst TiO2 NPs powders in a basic glucose solution were investigated. The electrocatalytic activity and stability of the loaded Au NPs/TiO2 NPs-N2 powder on the working electrode for the electrocatalytic oxidation of glucose were astonishingly high. The Au NPs/TiO2 NPs-N2 catalyst demonstrated electrocatalytic characteristics that were superior to a commercially available polycrystalline gold electrode in the application involving glucose alkaline fuel cells.